The impact of diaspora ventures on the dynamics of the start-up ecosystem Berlin - Baron, Thomas (Springer Gabler, 2017)
This book brings together the research fields of start-up ecosystems and diaspora entrepreneurship. The author interprets the results of semi-structured interviews with four diaspora entrepreneurs and four experts in Berlin, as well as observations from field studies and the analysis of secondary sources. The findings prove impacts of diaspora ventures on the dynamics of the Berlin start-up ecosystem and are applied to a modified version of the ANDE toolkit. Identified domains of the start-up ecosystem Berlin are demonstrated. Berlin is among the top locations of start-up activities world-wide and currently the most dynamic ecosystem globally. Contents " Berlin - the New Start-up Hotspot " Concept and Definition of a Start-up Ecosystem " Diaspora Entrepreneurship and Diaspora Research " Impacts on the Dynamics of the Start-up Ecosystem Berlin " Limitations and Future Research Target Groups " Researchers and students in the field of entrepreneurship, entrepreneurial ecosystems, diaspora and migration entrepreneurship " Policy makers and regional development agencies with interest in developing supportive environments for entrepreneurship The Author Thomas Baron is a research assistant at the Chair of Small Business and Entrepreneurship (LEMEX) at the University of Bremen. His research focuses on Entrepreneurial Ecosystems.
Keywords: New business enterprises -- Germany -- Berlin.; Germany -- Berlin.; elektronické knihy; electronic books